Sex and the Economics Student - Siegfried, John J.; Strand, Stephen H. (The Review of Economics and Statistics, 1977)
Previous efforts to examine the relationship between sex and student performance in college level introductory economics have generally found that males seem to perform significantly better on final examinations than females. Bach and Saunders (1965), Attiyeh, Bach and Lumsden (1971), Attiyeh and Lumsden (1971), Saunders (1971), Bolch and Fels (1974), and Clauretie and Johnson (1975) all found empirical support for the superior performance of males. The results are consistent across a variety of test instruments, including TUCE, TEU, TEC and CLEP.' Bolch and Fels (1974) have explained why contrary evidence from Buckles and McMahon (1971), Danielson and Stauffer (1972), and Lewis and Dahl (1972) is not convincing. The standard hypothesis underlying these empirical tests is that female students have grown up in a cultural environment in which girls are not supposed to like business and thus have a disadvantage in business or economics courses. More recently Garron (1970) has argued that the difference between male and female performance in learning spatial and numerical skills, which are related to understanding economics, is chromosome linked. This analysis tests these hypotheses once again, using a sample of 153 students from Vanderbilt University in Spring 1975. These new tests have advantages over those previously performed.' First, we employ a test instrument which is targeted at the course material scheduled to be taught in the experimental course. A well targeted exam is desirable because tests that include material with which students are unfamiliar are apt to measure intelligence rather than learning in the introductory economics course. Second, we examine the hypothesis separately for students who took the course in a conventional lecture-discussion type format and students who elected a personalized, self-paced method of instruction (PSI) (see Fels, 1974). Third, previous studies have typically used a final examination score as the indicator of performance. Final exam scores measure the level of understanding and comprehension of economics principles at the end of the course, but do not necessarily accurately reflect learning that took place during the instructional period. Our improved measure of learning is a construct, namely the percentage of the gap between a pre-test score3 and one hundred percent that is closed by a student during the semester.4 This value added type measure is more appropriate for testing hypotheses regarding the relationship between sex and learning during the introductory economics course.5 The results of multiple linear regression analysis using both final exam score and the gap closing measure as a dependent variable are reported in table 1. The independent variables are self-explanatory. Scholastic Aptitude Tests, and grade point average are statistically significant factors in determining performance for most of the regression models. This finding is consistent with earlier studies (see Bolch and Fels, 1974). In addition to the standard explantory variables in models of this type we include a binary variable which distinguishes whether either parent worked in a business related occupation on the grounds that such a situation would provide an environment more receptive toward learning business related skills. Concurrent credit hours are included to allow for the possibility that other demands on students' time during the experimental semester might have caused poor performance as students substituted study on other courses for studying economics. Neither of these hypotheses received empirical verification. Using a one-tail test (hypothesizing that males perform better than females), both the pooled and conventional final exam score regressions show a Received for publication October 9, 1975. Revision accepted for publication September 9, 1976. * This paper is part of an evaluation of the personalized self-paced case-method of instructing elementary economics, supported by the Joint Council on Economic Education and Vanderbilt University. The authors benefited from comments on an earlier draft by Ben Bolch, Steve Buckles, Rendigs Fels and Cliff Huang. 'Test of Understanding in College Economics, Test of Economics Understanding, Test of Economics Comprehension, and College Level Examination Program, respectively. 2This examination is a twenty-five question, multiple choice test called the Test of Elementary Economic Analysis (TEEA). It consists of eight recognition and understanding questions and seventeen application questions. The questions cover scarcity and efficiency (20%o), supply and demand (24%9o), national income accounting and analysis (28%7o), money and banking (16%o), and international finance (12%o). The examination was developed at Vanderbilt, pretested for several semesters, and revised in view of item analysis results. 3The pre-test consisted of the same 25 item multiplechoice exam administered on the first day of classes. I Performance = (post-test pre-test)/(100 pre-test). 'This measure was, to our knowledge, first proposed by Whitney (1960). [2471